Clinical and radiological outcomes with PEEK suture anchors used in rotator cuff repair: our experience confirm that a perianchor fluid signal on RM does not affect clinical outcome at one year of follow up - Di Benedetto, Paolo (Acta Biomed, 2020)
INTRODUCTION / OBJECTIVES: Osteolytic-type reactions of the perianchor bone which in magnetic resonance are manifested as hyperintensity of the signal in T2 images are reported in many studies. The doubt that this reaction of the bone could result in a loss of pull-out in the short and medium term and that it could therefore negatively affect tendon healing is the subject of an increasing number of studies. An osteolytic type signal around absorbable anchors can be explained by the metabilic processes in progress foreseen by the very nature of the material used, however this type of signal is also recognized around sutured implants or made of notoriously inert material. The objective of the present study is to evaluate and compare to the literature data the clinical and radiological results of a group of patients who underwent arthroscopic suture of a rotator cuff tear using polyetherketone (PEEK) suture anchors. MATERIALS AND METHODS: Twenty patients, aged between 44 and 73 years, who underwent arthroscopic repair of the rotator cuff for lesions smaller than 4 cm considered reparaible between August 2017 and January 2019, were enrolled in the present study. Patients were evaluated clinically with clinical examination, Constant scale and ASES scale pre and post surgery. MRI either pre and post operation at one year were evaluated to obtain data about tendon healing and evaluate bone reaction to PEEK anchors. RESULTS: The mean lesion size was 16.8 mm +/- 7.8 mm and the mean tendon retraction was 15.6 mm +/- 14.9 mm. The mean increase in Constant and ASES scores at the one year-follow up was respectively 36.8 (p<0.01) and 47.2 (p<0.01). MRI analysis showed a tendon signal according to Sugaya classification of type 1 in the 25% of patients, type 2 in the 60% of cases and type 3 in the remaining 15% . Osteolysis was grade 0 in 65%, grade 1 in 30 % and grade 2 in 5% of cases. No anchors pull out or mobilization were reported. CONCLUSIONS: The presence of a T2 hyperintense signal osteolysis like on MRI control using PEEK anchors for the sutur of rotator cuff lesions does not find correlation whit the final clinical result of the procedure. Indeed, both patients with a major degree of osteolysis and those with degree 0 had an improvement both in terms of clinical and scores evaluation and in termsof tendon healing according to Sugaya’s score found in our cohort. (www.actabiomedica.it)